Koncepcja osobowości Aleksandra Łazurskiego: od skłonności do relacji. Problem osobowości: Petersburska Szkoła Psychologiczna - Leontiev, Dmitry; Kondrat, Aleksandra (Kultura-Społeczeństwo-Edukacja, 2020)
Leontiev Dmitry, Aleksander Lazursky’s personality concept: from inclinations to relations. Problem of personality: Petersburg School of Psychology. Culture – Society – Education no 2(16) 2019, Poznań 2019, pp. 55–69, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2019.16.4. The article discusses the dynamics of psychological views of A.F. Lazursky (1874-1917), author of one of the first theories of personality in the world of psychology. There are two stages in Lazursky’s work: the first is associated with the concept of nature as an internal individually-typological basis of personality, and the second one is determined by introduction and more intensive development of ideas about an attitude towards the world as an important component of the personality structure. The primary aim of the article is to highlight the role of Lazursky in international psychology.